Photocatalytic degradation of glyphosate using Ce/N co-doped TiO2 with oyster shell powder as carrier under the simulated fluorescent lamp - Zhang, Wei; You, Qizheng; Shu, Jinkai; Wang, Aihe; Lin, Hai; Yan, Xuchao (Frontiers in Environmental Science, 2023)
Glyphosate is currently one of the most used organophosphorus herbicides in the world and its accumulation and translocation in soil and wave causes environmental pollution and biological health problems. A new approach to the problem is provided by the preparation of cerium and nitrogen co-doped titanium dioxide composite nano-photocatalysts loaded on modified oyster shell powder (CeNT@Oys) by a simple hydrothermal synthesis. The physicochemical and optoelectronic properties are analyzed using SEM, BET, XRD, Raman, FTIR, UV-vis DRS, XPS characterization techniques and a range of photoelectrochemical techniques. The results show that the addition of modified oyster shell powder increases its specific surface area, while Ce-N-TiO2 is an anatase crystal composed of Ce doped in the form of interstitial and surface, interstitial form of N, and the co-doping of Ce and N elements gives it the property of being excited by visible light. The photocatalytic activity of the different catalysts was evaluated by degrading 50 mg/L glyphosate solution under simulated sunlight. The catalyst was determined to be reusable by five repeated degradation experiments. Based on quenching experiments and the electron paramagnetic resonance (EPR) tests, the effective active species of glyphosate degraded by the catalyst was determined and the mechanism of glyphosate degradation by photocatalyst was proposed. Finally, the degradation pathway for the photocatalytic degradation of PMG by CeNT@Oys was determined by HPLC-MS/MS determine of the intermediate products.